Структура та властивості металу зони термічного впливу зварних з’єднань високоміцних спеціальних сталей - Grigorenko, G. M.; Zuber, T. A.; Kostin, V. A.; Poznyakov, V. D. (Physico- Technological Institute of Metals and Alloys of the NAS of Ukraine, 2018)
The built in thermokinetic diagrams of austenite decomposition are established and the influence of the cooling rate of samples of the HAZ metal imitators on the structure and strength properties of high-strength steels Quardian 500 and Armstal 500 is established. For Quardian 500 and Armstal 500 steels, the regularities of the influence of carbon content on the structure formation in the HAZ metal steel have been established and the propensity to brittle failure has been estimated. The conducted complex of studies showed that for high- strength Quardian 500 steel with a carbon content of 0.26 %, cooling in the V range from 20 to 30 °C/c leads to the formation in the over-heating zone of a predominantly martensitic structure and an increase in hardness from 4850 to 4890 MPa, which provides an increase in static strength. At that time, as for steel Armstal 500 with a heavier carbon content 0.29 %, cooling in the V range from 7 to 30 oC/c leads to the formation in the over-heating zone of a predominantly martensitic structure and an increase in hardness from 5160 to 5390 MPa.